Suggestions for resin research under the COST Action EU-PoTaRCh [version 1; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Jakub Brózdowski; Vítor João Pereira Domingues Martinho (Open Research Europe)
Forest management and planning is not an easy task due to, often, some intermittence in the incomes obtained by the landowners. In fact, namely in timber production, the producers must wait years to get revenues from the investments carried out on the lands they use. These frameworks become forest activities, in some circumstances, not attractive for the investors and, consequently, for adjusted management. The forest by-products appear as an opportunity to increase the profitability of the forest lands and motivate the land owners for more effective planning. This is crucial, namely in countries where forest fires, for example, are real problems for economic activity, populations and the environment. In this context, this study, developed within the scope of the COST Action PoTaRCh, intends to bring more insights and suggestions for the scientific research about resin. For that, a search was performed in the Scopus database (article title, abstract, keywords), on 02 November 2024, for the following topics: “natural resin” or “plant resin”. In this search, 4127 documents were obtained and assessed through bibliometric analysis. The findings identified reveal relevant gaps and trends in the literature that could be interesting outputs, particularly to support future research related to the different dimensions of resin worldwide.